2018
DOI: 10.1007/s00384-018-3141-4
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk prediction in the era of enhanced recovery: a comparison of POSSUM, ACPGBI, and E-PASS scoring systems in major surgical procedures of the colorectal surgeon

Abstract: PurposeThis study aims to determine whether traditional risk models can accurately predict morbidity and mortality in patients undergoing major surgery by colorectal surgeons within an enhanced recovery program.MethodsOne thousand three hundred eighty patients undergoing surgery performed by colorectal surgeons in a single UK hospital (2008–2013) were included. Six risk models were evaluated: (1) Physiology and Operative Severity Score for the enumeration of Mortality and Morbidity (POSSUM), (2) Portsmouth POS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…This study proves that POSSUM can accurately predict the incidence of postoperative complications in elderly patients subjected to hepatobiliary and pancreatic surgery, but it overestimates the mortality rate of patients. These results are consistent with those of Bagnall et al 14 Furthermore, this study proves that P-POSSUM can accurately predict the postoperative mortality rate. These results are consistent with the research of Nag et al 15 and Carvalho-E-Carvalho et al, 16 who indicated that P-POSSUM can be used as a tool to predict postoperative mortality rate.…”
Section: Discussionsupporting
confidence: 93%
“…This study proves that POSSUM can accurately predict the incidence of postoperative complications in elderly patients subjected to hepatobiliary and pancreatic surgery, but it overestimates the mortality rate of patients. These results are consistent with those of Bagnall et al 14 Furthermore, this study proves that P-POSSUM can accurately predict the postoperative mortality rate. These results are consistent with the research of Nag et al 15 and Carvalho-E-Carvalho et al, 16 who indicated that P-POSSUM can be used as a tool to predict postoperative mortality rate.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, data on specific scores evaluating patients at risk for surgery as ColoRectal Physiological and Operative Severity Score for the enumeration of Mortality and Morbidity (CR-POSSUM) score, were not included in data collection. Although colorectal CR-POSSUM and other frailty indexes[11] have proved to identify patients at risk for possible failure of ERPs[24,35], these scores tend to overestimate morbidity and mortality, since firstly elaborated for open surgery[36]. Considering this drawback and the limited use in clinical practice, such information was not considered in data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Existing prediction models using preoperative and intraoperative variables identify patients at higher risk of death. 29,30 Most of these models are either complex, using many variables and rendering them unpractical for bedside use; or are old and do not consider the advances in minimally invasive techniques and more recent enhanced post-operative recovery programs.…”
Section: Artigo Originalmentioning
confidence: 99%